De novo assembly and comprehensive characterization of the skeletal muscle transcriptomes of the European anchovy (Engraulis encrasicolus) - (:unkn) unknown (ELSEVIER, 2015)
European anchovy has considerable economic and ecological importance due to its high reproduction capacity and growth rate. As one of the largest source of wild marine protein, an increasing muscle mass strength has a major contribution to this growth rate during transition from subadult to adult stage. In the present study, using Illumina sequencing technology (HiSeq2000) accompanied with appropriate bioinformatics softwares; we have sequenced, assembled and annotated the transcriptome of wild subadult and adult anchovy muscles. A total of 131,081,776 high-quality reads were assembled into 125,506 contigs with an average length of 709.35 bp and N50 length of 1159 bp. Functional annotations of assembled contigs have been summarized according to 3325 GO terms, 3370 PFAM domains and 378 predicted KEGG metabolic pathways. About 11% of all contigs had at least one type of SSR motif in their sequences. According to the sequence homology analysis by BlasTN it was concluded that the assembled contigs include 16 skeletal muscle-expressed miRNAs, 14 ncRNAs and most of sarcomeric/myofibrillar genes. We hope that the sequence information regarding the muscle transcriptome of anchovy can provide some insight into the understanding of genome-wide transcriptome profile of teleost muscle tissue and give useful information in fish muscle development. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anchovy; Muscle; Transcriptome; Sequencing; De novo assembly; TOOL